Development Of Islamic Boarding School-Based Teaching Modules To Improve Mathematics Problem Solving Ability - Izza Luklu'ul Wafiroh (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to develop a teaching module based on islamic boarding school and a valid, practical, and effective solution skill test question. This type of research is development research using the Thiagarajan 4D development model. The data collection techniques used were Observation of the implementation of learning devices, student observation, test results of mathematical problem-solving ability, and student response questionnaires. The research subjects consisted of 21 students in the large-scale trial class, 6 students in the small-scale trial class, 23 students in the experimental class, and 23 students in the control class. The findings of this study are that the teaching modules developed have valid, practical, and effective criteria. Validity obtained from the teaching module validity coefficient in format, content, and language are 3.57, 3.62, and 3.60, respectively. The practicality of the teaching module obtained from the Observation of learning implementation reached 92.5%. The results of student activity observations amounted to 90.5%, with an outstanding category. Furthermore, the third indicator in the practicality test is obtained from the results of the student response questionnaire with a total score of 699 and a percentage of 92.46% with an outstanding category. The effective criteria are based on the test results with a classical completeness of 84.7%. In addition, the teaching module developed can affect improving students' mathematical problem-solving ability based on statistical tests and pretest and posttest scores of experimental and control classes obtained Sig. (2-tailed) = 0.000 (Sig.<0.05). Therefore, the teaching module based on islamic boarding school is valid, practical, effective, and influential.